2012
DOI: 10.1371/journal.pone.0038864
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Coding Synonymous and Non-Synonymous Variants in ADAMTS13 Using Ex Vivo and In Silico Approaches

Abstract: Synonymous variations, which are defined as codon substitutions that do not change the encoded amino acid, were previously thought to have no effect on the properties of the synthesized protein(s). However, mounting evidence shows that these “silent” variations can have a significant impact on protein expression and function and should no longer be considered “silent”. Here, the effects of six synonymous and six non-synonymous variations, previously found in the gene of ADAMTS13, the von Willebrand Factor (VWF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 78 publications
3
54
0
Order By: Relevance
“…These 2 common ADAMTS13 variants have been examined in 2 previous studies. One study examined expression and secretion of Q448E in cell culture and found results similar to those of our study but an increased specific activity of this variant compared with wild-type, 39 and another article examined both the Q448E and A732V variants expressed in cell culture and found similar decreases in secretion into culture media and ;25% reduction in enzyme activity as measured by a collagen binding assay. 40 However, both previous studies used transient transfection methods which may have altered patterns of synthesis and secretion compared with our experiments in cell lines with stable expression from the same locus.…”
Section: Discussionsupporting
confidence: 81%
“…These 2 common ADAMTS13 variants have been examined in 2 previous studies. One study examined expression and secretion of Q448E in cell culture and found results similar to those of our study but an increased specific activity of this variant compared with wild-type, 39 and another article examined both the Q448E and A732V variants expressed in cell culture and found similar decreases in secretion into culture media and ;25% reduction in enzyme activity as measured by a collagen binding assay. 40 However, both previous studies used transient transfection methods which may have altered patterns of synthesis and secretion compared with our experiments in cell lines with stable expression from the same locus.…”
Section: Discussionsupporting
confidence: 81%
“…1 However, an independent causal relationship between ADAMTS13 levels could not be established because of the unavailability of prospective studies. Recent studies aiming at the characterization of single nucleotide variants in ADAMTS13 through mRNA studies and in silico approaches 9,10 suggest that single nucleotide variants in ADAMTS13 influence its gene expression in a complex fashion, thus explaining interindividual variability in ADAMTS13 activity beyond nonsynonymous coding mutations affecting vWF-cleaving properties.…”
mentioning
confidence: 99%
“…Fluorogenic FRETS-VWF73 (Peptides International; Louisville, KY, USA) was prepared and assayed (Sauna et al, 2009). The kinetic characteristics of ADAMTS13 were obtained using GraphPad Prism software.ADAMTS13 sequencing revealed both children to be homozygous and their parents to be heterozygous for the previously described, cTTP-causing, single-base-substitution mutation 20506C > T (Table IA) (Levy et al, 2001;Snider et al, 2004;Hing et al, 2013). The children's VWF-CPase antigen and activity levels were undetectable, although steady-state levels of the ADAMTS13 mRNA were >2Á5-fold higher in the daughter than in the son.…”
mentioning
confidence: 90%
“…While prior studies have shown that the synonymous (s)-and ns-SNVs 3944C > T (c.864C > T ⇒ 140Ala > Ala) and 23789C > T (c.3143C > T ⇒ 900Ala > Val), respectively, are associated in vitro with no or only minor effects on VWF-CPase secretion compared to their more frequent wildtype alleles (Plaimauer et al, 2006;Edwards et al, 2012), the seven other allelically distinct, parental ADAMTS13 potential quantitative-trait nucleotides (QTNs) have never been experimentally investigated, individually or in combination with each other. The candidate functional SNVs, 11610G > C (IVS10[-32G > C]) and 18320G > A (IVS15[-26G > A]), are located in intronic regions known to contain cis-elements comprising 3'-splice junctions, and their alleles may, for example, influence precursor mRNA processing differentially.…”
mentioning
confidence: 99%